A study of the Problems of Luoshan Shadow puppet Creative Product Design - Xu, Taotao; Musdi, Shanat (2023)
With a long history and rich cultural connotation, Luoshan Shadow puppet has become an intangible cultural heritage of China. However, in the midst of modernisation, there are some problems with the design of Luoshan shadow creative products. In this paper, we examined an overview of research into the Luoshan shadow creative products. These products have been criticised for their lack of creativity in all design activities, which has hindered their development. In order to obtain more reliable results, we chose to conduct an extensive questionnaire survey in China. A descriptive analysis of all user data from these questionnaires was carried out. 379 participants' data showed the theme of this study; i. problems of stylistic design; ii. problems of lack of distinctiveness; and iii. problems of overpricing. These findings are beneficial to further research on the innovative design of Luoshan shadow creative products.